2009
DOI: 10.1038/cr.2009.80
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of TRAIL cytotoxicity by AG-490 in human ALL cells is characterized by downregulation of cIAP-1 and cIAP-2 through inhibition of Jak2/Stat3

Abstract: The ability of death-inducing tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) to selectively kill a variety of cancer cells has been largely described, but one of the major concerns with the treatment is the occurrence of drug resistance and possible toxic side effects. Here, we report that TRAIL induces apoptosis in Jurkat and SUPT1 T cell lines and in human T-ALL blasts but not in healthy subject-derived peripheral blood mononuclear cells. In parallel, the treatment with TRAIL and Tyrphostin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 52 publications
1
17
1
Order By: Relevance
“…We found that STAT3 inhibition by AG490 induced PEL cell apoptosis mainly involving the extrinsic pathway. Interestingly, it has been recently shown that AG490 synergizes with tumor necrosis factorrelated apoptosis-inducing ligand (TRAIL) in the induction of apoptotic cell death in Jurkat and Acute Lymphoblastic Leukemia (ALL) cells [29]. Concomitant to apoptosis induction, AG490 dephosphorylated STAT3 and down-regulated HSP70 and HSF1, the main HSP transcription factor, in PEL cells.…”
Section: Discussionmentioning
confidence: 98%
“…We found that STAT3 inhibition by AG490 induced PEL cell apoptosis mainly involving the extrinsic pathway. Interestingly, it has been recently shown that AG490 synergizes with tumor necrosis factorrelated apoptosis-inducing ligand (TRAIL) in the induction of apoptotic cell death in Jurkat and Acute Lymphoblastic Leukemia (ALL) cells [29]. Concomitant to apoptosis induction, AG490 dephosphorylated STAT3 and down-regulated HSP70 and HSF1, the main HSP transcription factor, in PEL cells.…”
Section: Discussionmentioning
confidence: 98%
“…Lanuti et al (43) previously reported that the combinatorial effect of TRAIL and AG490 on T-cell leukemia was characterized by a significant inhibition of STAT3 phosphorylation compared with the controls or TRAIL alone-treated samples (43). However, cell viability, CASP3 activity and TUNEL assay results of the present study showed that LNCaP cells are resistant to TRAIL-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other evidences suggest that c-IAP-1 and c-IAP-2 are also important targets for T-ALL therapy. Thus, incubation of T-ALL blasts with A490, a JAK-2 inhibitor, inhibited Stat3 phosphorylation, greatly reduced c-IAP-1 and c-IAP-2 levels and enhanced TRAIL-induced apoptosis [Lanuti et al, 2009]. Another approach was proposed for B-ALL, based on the use of a TRAIL fusion protein designated scFvCD19:sTRAIL, consisting of a CD19-speciifc single-chain Fv antibody fragment (scFv) fused to the soluble extracellular domain of TRAIL (sTRAIL).…”
Section: Acute Lymphoblastic Leukemia (Alls)mentioning
confidence: 94%